2020
DOI: 10.1371/journal.pbio.3000561
|View full text |Cite
|
Sign up to set email alerts
|

Nanog safeguards early embryogenesis against global activation of maternal β-catenin activity by interfering with TCF factors

Abstract: Maternal β-catenin activity is essential and critical for dorsal induction and its dorsal activation has been thoroughly studied. However, how the maternal β-catenin activity is suppressed in the nondorsal cells remains poorly understood. Nanog is known to play a central role for maintenance of the pluripotency and maternal-zygotic transition (MZT). Here, we reveal a novel role of Nanog as a strong repressor of maternal β-catenin signaling to safeguard the embryo against hyperactivation of maternal β-catenin a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 95 publications
(138 reference statements)
1
10
0
Order By: Relevance
“…ScRNA sequencing (scRNA-seq) of zebrafish, Xenopus , primates (i.e., human and marmoset) embryos highlights the importance of vsDPGs as part of the refractory/naïve pluripotency gene regulatory network (GRN) [ 24 , 25 , 37 , 38 , 39 , 53 ]. It also confirms functional analyses in vivo and in vitro showing that vsDPGs have crucial functions in maintaining pluripotency and counteracting spontaneous and precocious PSCs differentiation [ 14 , 16 , 17 , 21 , 22 , 26 , 27 , 28 , 33 , 34 , 35 , 36 , 54 , 55 ].…”
Section: Role Of Developmental Potential Guardians In Stem Cells Plur...supporting
confidence: 78%
See 4 more Smart Citations
“…ScRNA sequencing (scRNA-seq) of zebrafish, Xenopus , primates (i.e., human and marmoset) embryos highlights the importance of vsDPGs as part of the refractory/naïve pluripotency gene regulatory network (GRN) [ 24 , 25 , 37 , 38 , 39 , 53 ]. It also confirms functional analyses in vivo and in vitro showing that vsDPGs have crucial functions in maintaining pluripotency and counteracting spontaneous and precocious PSCs differentiation [ 14 , 16 , 17 , 21 , 22 , 26 , 27 , 28 , 33 , 34 , 35 , 36 , 54 , 55 ].…”
Section: Role Of Developmental Potential Guardians In Stem Cells Plur...supporting
confidence: 78%
“…Biochemical and molecular studies in vivo demonstrated that VENTX-POU5 and NANOG-POU5 proteins physically interact as a heterodimer to control transcription of genes required for germ layer commitment, patterning and morphogenesis ( Figure 2 A) [ 16 , 26 , 27 , 28 , 33 , 34 , 35 , 36 , 54 ]. VsDPGs heterodimer physically interact also with SMADs proteins (effectors of the TGFβ NODAL/ACTIVIN and BMPs signaling pathways), as well as with CTNNB1 (β-CATENIN)-TCF/TLE proteins (effectors of the WNT signaling pathway) [ 21 , 26 , 27 , 33 , 34 , 35 , 36 , 54 ].…”
Section: Role Of Developmental Potential Guardians In Stem Cells Plur...mentioning
confidence: 99%
See 3 more Smart Citations